Three new earthworm species of the genus Amynthas (Clitellata: Megascolecidae) from Mt. Chiak National Park, Korea - Hong, Yong; James, Samuel W. (Zootaxa, 2013)
Earthworm specimens collected from Mt. Chiak, National Park, Korea were found to represent three new species of megascolecid earthworms: Amynthas chiakensis sp. nov., Amynthas gyeongriae sp. nov., and Amynthas wonjuensis sp. nov. Amynthas chiakensis sp. nov. has two pairs of spermathecae in VII and VIII, small transverse oval male porophores each with C-shaped small patches of genital papillae, 0.22–0.31 circumference apart. Amynthas gyeongriae sp. nov. has spermathecae in VI–VIII, male field with large circular-shaped raised pads and seminal grooves, with pores 0.16–0.28 circumference apart. Amynthas wonjuensis sp. nov. has spermathecae in VI and VII, male pores superficial in XVIII on small oval-shaped white porophores lateral to large roughly circular raised genital papillae, 0.15 circumference apart.